Minimalisasi Bahan Baku yang Terbuang melalui Mixer di PT CPI Balaraja - Kevin Yapania Claudia; Tanti Octavia (Jurnal Titra, 2015)
PT Charoen Pokphand Feedmill Balaraja Indonesia is a poultry feed producer company. One of the main processes in feed production is mixing process which involves mixer machine. When mixing process is running lot of raw material wasted out through the mixer machine funnel. The wasted raw material known as bin has a low selling price which brings losses to the company. DMAIC is applied to solve the problem.Improvement carried out by installing hostaform to cover the gap that allows the raw material wasted out from the mixer machine through the funnel and change the handle position. Result of the improvement is the amount of raw materials that wasted out through the funnel was reduced by 80.02% with cost needed is Rp. 6.109.703,-. The company can save Rp. 442.911.432,-/year by implementing this improvement. Control to the improvement is needed every two months, according to the mixer machine preventive schedule.